2019
DOI: 10.3389/fgene.2019.00710
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Differential Expression of Genes Regulating Hepatic Triglyceride Metabolism in Pekin Ducks During Dietary Threonine Deficiency

Abstract: Dietary threonine (Thr) deficiency increases hepatic triglyceride accumulation in Pekin ducks, which results in fatty liver disease and impairs hepatic function. However, the underlying molecular mechanisms altered by dietary Thr deficiency are still unknown. To identify the underlying molecular changes, 180 one-day-old ducklings were divided into three groups, including Thr deficiency group (Thr-D), Thr sufficiency group (Thr-S), and pair-fed group (Pair-F) that was fed with a Thr-sufficient diet but with red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 101 publications
3
15
0
Order By: Relevance
“…Recently, in our laboratory, it was evaluated that threonine requirement is 0.61% for Pekin duck from 1 to 21 D of age. Meanwhile, we also observed that dietary threonine deficiency would increase hepatic total lipids of Pekin ducks ( Jiang et al., 2017 , Jiang et al., 2019a ) and hepatic fatty acid profile contents ( Jiang et al., 2019b ). Whether dietary threonine supplementation affects fatty acid profile contents of breast muscle and responses of fatty-type duck to dietary threonine levels are similar to those of lean-type duck is still unknown.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, in our laboratory, it was evaluated that threonine requirement is 0.61% for Pekin duck from 1 to 21 D of age. Meanwhile, we also observed that dietary threonine deficiency would increase hepatic total lipids of Pekin ducks ( Jiang et al., 2017 , Jiang et al., 2019a ) and hepatic fatty acid profile contents ( Jiang et al., 2019b ). Whether dietary threonine supplementation affects fatty acid profile contents of breast muscle and responses of fatty-type duck to dietary threonine levels are similar to those of lean-type duck is still unknown.…”
Section: Introductionmentioning
confidence: 80%
“…Meanwhile, dietary threonine deficiency increased plasma HDLC and TCHO concentrations. A previous study from our laboratory showed that dietary threonine deficiency increased the gene expression related to fatty acid and triglyceride synthesis, and reduced the gene expression involving in fatty acid oxidation and triglyceride degradation ( Jiang et al., 2019b ), although it did not detect the changes of genes related to lipid transportation to extrahepatic tissue, we speculated that threonine deficiency influences the transfer of lipid from liver to blood by decreasing the protein synthesis in lean-type ducks, hence the lipid was deposited in the liver. Whereas, threonine-deficient diet reduced hepatic total lipids in rat ( Ross-Inta et al., 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Thr may also regulate lipid metabolism, by reducing plasma triglyceride level when supplemented at 64% ADF Thr-to-Lys ratio compared to the other Thr levels in the present study. Jiang et al., 2017 , Jiang et al., 2019 suggested that dietary Thr supplementation improved hepatic lipid metabolism of Pekin ducks by regulating lipid synthesis, transport and oxidation. Similar observations were found in mammals ( Yoshida et al., 1961 ; Xiao et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Essential amino acids have a close connection with the lipid metabolism, whereby certain amino acids (methionine, leucine, and isoleucine) can affect lipid deposition [ 23 ]. Thr similarly takes part in regulating lipid metabolism and deposition [ 24 ]. Thr supplementation has been shown to enhance hepatic lipid metabolism, while Thr deficiency may induce hepatic triglycerides accumulation, as shown in previous research [ 8 ].…”
Section: Role Of Thr In Nutrition Metabolismmentioning
confidence: 99%
“…Research on Pekin ducks found that dietary Thr shortage increased the expression of genes encoding 3-oxoacyl-ACP synthase ( OXSM ), very-long-chain fatty acids protein 7 ( ELOVL7 ), and long-chain fatty acyl-CoA ligase ( ACSBG2 ), which were related to fatty acid and triglyceride synthesis. However, genes participating in fatty acid oxidation, such as acyl-CoA dehydrogenase, acyl-CoA dehydrogenase family member 11 ( ACAD11 ) and cytochrome P450 ( CYP4B ), as well as genes associated with fatty acid and triglyceride transport, acyl-CoA binding protein ( DBI ), apolipoprotein D ( APOD ), and microsomal triglyceride transfer protein ( MTTP ), were downregulated under Thr deficiency in Pekin ducks [ 24 ]. The equilibrium between lipogenesis and lipolysis determines lipid homeostasis [ 25 ].…”
Section: Role Of Thr In Nutrition Metabolismmentioning
confidence: 99%